International Delphi Expert Consensus on Safe Return to Surgical and Endoscopic Practice: From the Coronavirus Global Surgical Collaborative - Asbun, HJ (Ovid Technologies (Wolters Kluwer Health), 2021)
10.1097/SLA.0000000000004674